Intensive glucose control and macrovascular outcomes in type 2 diabetes. - Turnbull, F; Abraira, C; Anderson, R; Byington, R; Chalmers, J; Duckworth, W; Evans, G; Gerstein, H; Holman, R; Moritz, T; Neal, B; Ninomiya, T; et al. (2009)
AIMS/HYPOTHESIS: Improved glucose control in type 2 diabetes is known to reduce the risk of microvascular events. There is, however, continuing uncertainty about its impact on macrovascular disease. The aim of these analyses was to generate more precise estimates of the effects of more-intensive, compared with less-intensive, glucose control on the risk of major cardiovascular events amongst patients with type 2 diabetes. METHODS: A prospectively planned group-level meta-analysis in which characteristics of trials to be included, outcomes of interest, analyses and subgroup definitions were all pre-specified. RESULTS: A total of 27,049 participants and 2,370 major vascular events contributed to the meta-analyses. Allocation to more-intensive, compared with less-intensive, glucose control reduced the risk of major cardiovascular events by 9% (HR 0.91, 95% CI 0.84-0.99), primarily because of a 15% reduced risk of myocardial infarction (HR 0.85, 95% CI 0.76-0.94). Mortality was not decreased, with non-significant HRs of 1.04 for all-cause mortality (95% CI 0.90-1.20) and 1.10 for cardiovascular death (95% CI 0.84-1.42). Intensively treated participants had significantly more major hypoglycaemic events (HR 2.48, 95% CI 1.91-3.21). Exploratory subgroup analyses suggested the possibility of a differential effect for major cardiovascular events in participants with and without macrovascular disease (HR 1.00, 95% CI 0.89-1.13, vs HR 0.84, 95% CI 0.74-0.94, respectively; interaction p = 0.04). CONCLUSIONS/INTERPRETATION: Targeting more-intensive glucose lowering modestly reduced major macrovascular events and increased major hypoglycaemia over 4.4 years in persons with type 2 diabetes. The analyses suggest that glucose-lowering regimens should be tailored to the individual.